An Analysis Students’ Pronunciation of Word Stress of The Second Semester Students of English Education Program of Nurul Huda University - Ainur Rohmah; Sargiya Septiana; Anisa Rahmawati; Anisfa Isnatun; Stya Kirana Zahrani (Departement of Mathematics Education, 2024)
In this study concerns with An Analysis Students’ Pronunciation of Word Stress of the Second Semester Students of English Education Program of Nurul Huda University. This study focused on the degrees of students’ pronunciation of word stress and to know the dominant degree of students’ pronunciation of word stress of the second semester students of English education program of Nurul Huda University. The writer used descriptive method to know the objective of the study that was the dominant degree of students’ pronunciation of word stress that were produced by the respondents. The technique for collecting the data were test consisted of 30 words and observation and the technique for analyzing the data are data reduction, data display and conclusion drawing/verification. Moreover, from the pronunciation of word stress there were two degrees of word stress such as primary stressed and unstressed. Based on the findings, the dominant degree of student pronunciation of word stress in this presented was unstressed because the highest degree of pronunciation test and observation is using unstressed and the lowest is using primary stressed with the total result of using primary stressed and correct was 278 (46,3%) words from 20 respondents and the lowest result with the total of using unstressed and incorrect was 322 (53,7%) words from 20 respondents. The primary stress and unstressed was different 44 (7,3%) words. The observation there were 9 (45%) words of 20 words was using primary stressed and there were 11 (55%) words of 20 words was using unstressed syllable. The students’ unstressed were quite similar. The words most unstressed made by the students was verbs because the student often using Indonesian accent to pronounce it and especially the student didn’t understand about the roles of words stress.